STUDENTS' PERCEPTION TOWARD THE USE OF ZOOM FOR TEACHING SPEAKING - Ilham Yasin (Language-Edu, 2021)
This study aimed to know and dig out the deep students’ perception using zoom in speaking skill as the alternative solution, whether the use of zoom as media in online learning in speaking class effective or ineffective during pandemic eras of COVID-19. The subject of this study were thirty of English department students at fourth semester of University of Islam Malang. The research was survey qualitative. The data collection technique was undertaken by giving questionnaires through Google Form and use the technique of deep interview using smartphone recording in zoom meeting. There were thirty students participated in giving questionnaire and there were nine students participated in undertaking the deep interview at fourth semester of English department University of Islam Malang.The data were analysed and interpreted through qualitative procedure. The findings indicated that the majority of students at fourth semester of English department have negative perception in using zoom in speaking skill as the alternative learning media in this pandemic of COVID-19. The result of this study indicates that the use of zoom in speaking class ineffectively to be used in speaking class, the use of zoom in speaking class could not give the students real social interaction and make the students to be a silent learner in speaking without having adequate feedback and special opportunity in conducting the discussion in speaking class. Keywords: Speaking skill, students’ perception, the use of zoom.